The Effectiveness of Web-Based Teaching Materials in Mandarin Subject - Mega; Sardianto Markos Siahaan; Somakim (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2022)
This study aimed to determine the effectiveness of web-based teaching materials about